2007
DOI: 10.1186/1471-2148-7-129
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of the MAGUK family in metazoan genomes

Abstract: Background: Development, differentiation and physiology of metazoans all depend on cell to cell communication and subsequent intracellular signal transduction. Often, these processes are orchestrated via sites of specialized cell-cell contact and involve receptors, adhesion molecules and scaffolding proteins. Several of these scaffolding proteins important for synaptic and cellular junctions belong to the large family of membrane-associated guanylate kinases (MAGUK). In order to elucidate the origin and the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 45 publications
5
81
0
Order By: Relevance
“…We confirmed that the mutation induces spindle orientation activity in an extant fungal GK enz (S35P; Saccharomyces enzyme numbering), a lineage that lacks MAGUKs [ Fig. 2A; (4,6)]. Thus, a single mutation is sufficient for the functional evolution of a nucleotide kinase to a spindle-orienting domain within the GK protein fold.…”
Section: Resultssupporting
confidence: 58%
“…We confirmed that the mutation induces spindle orientation activity in an extant fungal GK enz (S35P; Saccharomyces enzyme numbering), a lineage that lacks MAGUKs [ Fig. 2A; (4,6)]. Thus, a single mutation is sufficient for the functional evolution of a nucleotide kinase to a spindle-orienting domain within the GK protein fold.…”
Section: Resultssupporting
confidence: 58%
“…Structural and molecular studies have shown that PDZ domains are pivotal features of scaffolding proteins and localize MAGUKs and their interaction partners to specialized membrane domains of neuronal and epithelial cells (10,11). The domain architecture of the MAGUKs enables interaction with receptors, the actin cytoskeleton, and ion channels but also allows the tethering together of different MAGUK subfamily proteins (50), which may contain up to six PDZ domains (44).…”
Section: Discussionmentioning
confidence: 99%
“…Ca 21 /calcium/calmodulin-dependent serine protein kinase (CASK) is very similar in topology to the MPPs, with protein domains that include a catalytically active Ca 21 /calmodulindependent kinase domain at the amino-terminus followed by two L27 domains, a PDZ domain, an SH3 domain, and a GK domain (te Velthuis et al, 2007;Mukherjee et al, 2008) (Fig. 1).…”
Section: Containing Maguk Proteinsmentioning
confidence: 99%